Abstract The Repatriation of Rwandan Refugees: A Veritable Dilemma - Gachuruzi, Shally B. (Refuge: Canada’s Journal on Refugees, 1994)
This paper explores the problematic repatriation of Rwandan refugees and attempts to demonstrate that their return, in the absence of a durable peace, is not a definitive solution.